A sustainable drinking water supply from rainwater harvesting by submerge bio-membrane reactor - Ahmad Fakhirin, Ali (2010)
The world today is facing a serious water crisis.Anywhere in the world, water scarcity has become a major issue.Water is very important to the survival of mankind.Water is used for drinking,cooking,bathing, washing and land irrigation.Much solution has been design to solve the problems.Rain water harvesting is a great water conservation initiative as it reduces our dependence on main water supplies.However presence of undesirable colour taste and odours in rainwater resulting from micro pollutants and microorganism contamination such as suspended solids,colloidal materials, faecal and bacteria has demanded for extra pre-treatment prior to safe potable water consumption.Hence a study on the applicability of Bio-Membrane Reactor system for treating harvested rainwater to potable quality is carried out. National Drinking Water Quality Standard is used as guidelines in determine the rainwater quality.Both raw and treated sample is tested to reflect the rainwater quality and the efficiency of Bio-Membrane Reactor in treating the rainwater.The quality of rainwater is quite satisfactory with only arsenics level is exceeding the National Drinking Water Quality Standard.The level of colour,turbidity and E coli is under the maximum level.The Bio-Membrane Reactor is proving efficient in treating the rainwater when all parameter has been reducing to lower level.